Presynchronizing Prostaglandin F2α injection before timed artificial insemination CO-Synch + CIDR program - Hill, Scott L.; Pulley, Stephanie Leeann; Mellieon, H.I. Jr.; Olson, K. C.; Jaeger, John R.; Breiner, Ryan M.; Perry, G.A.; Lamb, G.C.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Fixed-time artificial insemination is an effective management tool that reduces the labor associated with more conventional programs that require detection of estrus. The 7-day CO-Synch + controlled internal drug release (CIDR) insert protocol has been shown to effectively initiate estrus and ovulation in cycling and non-cycling suckled beef cows, producing pregnancy rates at or greater than 50% in beef cows. The gonadotropin- releasing hormone (GnRH) injection that begins the CO-Synch + CIDR program initiates ovulation in a large proportion of cows, particularly anestrous cows. The CIDR, which releases progesterone intravaginally, prevents short estrous cycles that usually follow the first postpartum ovulation in beef cows. Our hypothesis was that inducing estrus with a prostaglandin injection 3 days before applying the 7-day CO-Synch + CIDR protocol might increase the percentage of cycling cows that would exhibit synchronous follicular waves after the onset of the CO-Synch + CIDR protocol, thereby increasing pregnancy outcomes.
Keywords: Beef; Prostaglandin F2α; Timed A.I.; CO-Synch + CIDR